IMPLEMENTASI ADOPSI DAN PERLINDUNGAN ADOPSI DITINJAU DARI HUKUM ISLAM - Devika Rosa Guspita (Karimiyah: Journal of Islamic Literature and Muslim Society, 2023)
Every child has rights and obligations as a child in the family, even in families with low economic levels this is often ignored, due to several socioeconomic conditions of the family that are not possible. This study aims to determine the implementation of adoption through social services and Islamic law, to determine the obstacles in the process of implementing child adoption and inheritance rights of children adopted from an Islamic perspective. This research is included in the type of qualitative research with a literature study approach. The analysis technique used is content analysis technique. The results of this study are 1) The implementation of child adoption at the Social Welfare Service of Cilegon City can be carried out in two ways, namely the appointment of single adoptive parents through social orphanages and through the Cilegon City Social Service. 2) An obstacle in the process of implementing child adoption through social services in the city of Cilegon is if there are religious differences between the prospective adopted child and the prospective adoptive parents. 3) Adopted children will never get inheritance rights from their adoptive parents and vice versa, but the scholars set a mandatory will as an inheritance solution for adopted children.